1998
DOI: 10.1164/ajrccm.158.1.9712017
|View full text |Cite
|
Sign up to set email alerts
|

Survival and FEV1Decline in Individuals with Severe Deficiency of α1-Antitrypsin

Abstract: Subjects >= 18 yr of age with serum alpha1-antitrypsin (alpha1-AT) levels <= 11 microM or a ZZ genotype were followed for 3.5 to 7 yr with spirometry measurements every 6 to 12 mo as part of a National Heart, Lung, and Blood Institute Registry of Patients with Severe Deficiency of Alpha-1-Antitrypsin. Among all 1,129 enrollees, 5-yr mortality was 19% (95% CI: 16 to 21%). In multivariate analyses of 1, 048 subjects who had been contacted >= 6 mo after enrolling, age and baseline FEV1% predicted were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(80 citation statements)
references
References 35 publications
6
71
0
3
Order By: Relevance
“…Although this study was small, it was enough for the product to gain a license for treatment of patients with the PiZ or null phenotypes [75] in the USA, Canada and parts of Europe. Observational work in the USA has since supported the use of AAT replacement, showing a slower decline in lung function in those with an FEV 1 of 35–49% predicted when receiving AAT augmentation [76]. Similar work in Europe has concurred [77, 78], whilst a Canadian study reported a beneficial effect but failed to show the association with baseline FEV 1 [79].…”
Section: Approaches To Treatmentmentioning
confidence: 99%
“…Although this study was small, it was enough for the product to gain a license for treatment of patients with the PiZ or null phenotypes [75] in the USA, Canada and parts of Europe. Observational work in the USA has since supported the use of AAT replacement, showing a slower decline in lung function in those with an FEV 1 of 35–49% predicted when receiving AAT augmentation [76]. Similar work in Europe has concurred [77, 78], whilst a Canadian study reported a beneficial effect but failed to show the association with baseline FEV 1 [79].…”
Section: Approaches To Treatmentmentioning
confidence: 99%
“…The largest observational study analyzed data from 1,129 patients in the US AATD registry split into three groups “always receiving” (n=390), “partly receiving” (n=357), or “never receiving” (n=382) augmentation 33. Dosing was not standardized with only 51.3% being dosed weekly throughout the study.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy-five patients had ≥1 exacerbation during the 18 months follow-up required prior to commencement of augmentation. Dosing regimens were not standardized with an average dose of 60.7±3.8 mg/kg/week (Table S1) different from other studies,33 and many patients had missing data. Fewer exacerbations were seen (1.2±1.6 vs 1.0±2.2 pre- vs posttreatment; P <0.01), an effect more marked in those exacerbating previously (2.0±1.6 vs 1.4±2.7; P <0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Any discrepancies between the results of the assay and the quantitative test, as shown before, should prompt the physicians to ask for a plasma IEF or a more sophisticated molecular approach, such as allele-specific amplification, or sequence analysis [4]. Another, minor clinical application of the amplification-reverse hybridization assay kit, is to confirm a ZZ genotype in patients in whom, in spite of lacking precise AAT characterization, AAT replacement therapy has already been started [14]. …”
Section: Discussionmentioning
confidence: 99%